Social network research in Africa. Issue 471 (9th January 2019) - Marks, Zoe; Stys, Patrycja
Abstract: Social network approaches have much to offer for the study of African politics. This research note explores the tensions and benefits of using social networks as metaphor or as method, and highlights the types of questions network research can address. We discuss sources of network data, key features of the graphical perspective and basic vocabulary, and the difference between analyzing individual networks and full systems. Three social network analysis (SNA) concepts—centrality, brokerage, and multilevel networks—indicate theoretic spaces for qualitative and quantitative synergies. The note also raises practical considerations and ethical challenges for conducting network research in fieldwork settings, drawing on a collaborative project in eastern Democratic Republic of the Congo. In conclusion, we encourage layering disciplines and mixing methods to more fully understand how networks shape social life in Africa.